Redefining global citizenship education: a case study of Kazakhstan (Journal of Philosophy Culture and Political Science, 2021)
One of the most important challenges in the educational system is effectively engaging young people to become educated and concerned citizens actively working on finding solutions to today’s pressing issues, from Sustainable Development Goals (SDGs), climate change and environmental pollution, to maintaining peace and security through development and communication. Recent work (UNESCO, 2015) suggests that global citizenship education (GCE) is increasingly becoming one of the tools not only for educating youth on global challenges, but also for involving them in implementation of SDGs, volunteership, and civil society activities. The purpose of this article is to analyze the evolving approaches in conceptualizing GCE, and incorporating it into curricula and extracurricular activities, using the example of Kazakhstan. The article addresses three research questions: First, how are researchers and educators conceptually redefining GCE in the learning environment of national higher education institutions (HEIs), educating youth on globalization and global challenges, and harmonizing the concepts and perceptions of national and global citizenship? Second, how do educators perceive the place of GCE in the traditional education programs within universities, and define the conceptual focus of different aspects of globalization and GCE within their teaching practice? And third, how do educators in the developing world integrate GCE into the existing traditional educational programs within universities, specifically in the case of Kazakhstan? This research offers a nuanced approach to the introduction of GCE in higher education institutions in the context of developing countries.Key words: Global Citizenship Education, Sustainable Development Goals (SDGs), Higher Education Institutions (HEI), Kazakhstan